2007
DOI: 10.1007/s11540-007-9030-9
|View full text |Cite
|
Sign up to set email alerts
|

Field Screening for Variation of Drought Tolerance in Solanum tuberosum L. by Agronomical, Physiological and Genetic Analysis

Abstract: Solanum tuberosum cultivars, Solanum tuberosum × Solanum tuberosum subsp. andigena hybrids and breeding clones with different time to maturity were screened for drought tolerance in field plots located in the coastal desert of Peru. Variation for drought tolerance was illustrated by clone-dependent differences in tuber yield and yield loss under drought conditions. Neither changes in stomatal conductance nor maximum quantum yield of chlorophyll fluorescence were quantitatively associated with yield or yield lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 43 publications
(45 reference statements)
8
64
1
Order By: Relevance
“…The tubers were graded into two categories; >25 g and < 25 g. Tubers <25 g category, and diseased, insect damaged, cracked, green, second growth, and early sprouted tubers were considered as non-marketable, and tubers of > 25 g with well-shaped tubers were considered as marketable tuber (NPRP, 2014). Drought susceptibility index was calculated as (1-yielddrought/yieldirrigated) / (1-meandroughted/meanirrigated) (Schafleitner et al, 2007). …”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tubers were graded into two categories; >25 g and < 25 g. Tubers <25 g category, and diseased, insect damaged, cracked, green, second growth, and early sprouted tubers were considered as non-marketable, and tubers of > 25 g with well-shaped tubers were considered as marketable tuber (NPRP, 2014). Drought susceptibility index was calculated as (1-yielddrought/yieldirrigated) / (1-meandroughted/meanirrigated) (Schafleitner et al, 2007). …”
Section: Measurementsmentioning
confidence: 99%
“…The reduction of marketable tuber number under drought stress was varied from 64% to 83% and most of tubers under drought plots were observed as malformed, reduced size with defected tubers (data not shown). Schafleitner et al (2007) had observed the malformed tuber in water deficit condition. Genotype by treatment interaction was significant.…”
Section: Marketable Tuber Numbermentioning
confidence: 99%
“…Reflectance indices were used to measure biomass and drought stress, changes in leaf water content (Francois and De Proft 2005) and water stress (Bahrun et al 2003). A set of drought tolerance genes previously found to be up-regulated in tolerant potato under drought (Schafleitner et al 2007) was assayed for expression changes in potato under drought.…”
mentioning
confidence: 99%
“…However, the leaf water potential results for the 2009/2010 study did not demonstrate genotypic variability on leaf water potential possibly due to low drought intensity compared to 2010/2011, when they differed in leaf water potential, as once reported in the Andean region between water regimes [33]. The 2009/2010 study finding illustrated that potato leaf water potential is not as sensitive as gaseous exchange to water stress and hence it was not a very reliable indicator for cultivar tolerance to water stress, as formerly observed [23].…”
Section: Discussionmentioning
confidence: 49%